HIPERLOCAL, DADOS E APLICATIVOS: inovações no fazer jornalismo e comunicação - COELHO, Aparecido Antonio dos Santos (2016)
Technological developments in contemporary communication structure digital systems through networks of connected computers and exploitation of technological devices. The digital data captured and distributed through applications installed on smartphones create dynamic communications environment. Journalism and communication are trying to adapt to the new information ecosystem entreated by constant technological innovations that allow the creation of new environments and systems access to information of social relevance. New tools for the production and distribution of content, based on data and intelligent interactions products, the algorithms used in the different processes, hyperlocals platforms and narrative and digital production systems. In this context, the objective of this study was to develop an overview with analysis and comparison between the products of the media and technology are the new technologies add attributes to the narrative and journalistic productions and its impact on the practice of activity. It also examines whether there are changes in the production processes of social interest information regarding processes and consolidated traditional journalism. Investigates the use of information inserted by users, in real time, it improves the quality of the narratives derived from mobile devices and if the gamification alters the perception of the credibility of journalism. For so be rethought the way to produce and generate information and knowledge for the public demanding content.